2006
DOI: 10.1007/bf03174070
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged treatment with the β3-adrenergic agonist CL 316243 induces adipose tissue remodeling in rat but not in guinea pig: 1) fat store depletion and desensitization of β-adrenergic responses

Abstract: Beta3-adrenergic agonists have been considered as potent antiobesity and antidiabetic agents mainly on the basis of their beneficial actions discovered twenty years ago in obese and diabetic rodents. The aim of this work was to verify whether prolonged treatment with a beta3-adrenergic agonist known to stimulate lipid mobilisation, could promote desensitization of beta-adrenergic responses. Wistar rats and guinea pigs were treated during one week with CL 316243 (CL, 1 mg/kg/d) by implanted osmotic minipumps. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
2
11
0
6
Order By: Relevance
“…Lipid content was gravimetrically determined after extraction in organic solvant as previously reported (16) Lipolytic activity of isolated adipocytes and glucose uptake into fat tissue pieces.-Freshly isolated white adipocytes were used for the determination of lipolytic activity, by assessing the glycerol release in incubation medium containing 3.5 % bovine albumin, as previously described (4). The results were expressed as percentage of responses to 10 nM isoprenaline, which is independent of fat cell size and basal triglyceride breakdown (9). The previously described technique used for the determination of 2-deoxyglucose uptake into adipocytes (8) was adapted to small pieces of adipose tissues, incubated without previous collagenase digestion, and separation between internalized hexose from extracellular was performed by successive washings as for muscle (19) instead of the centrifugation through dynonylphtalate layer used for buoyant fat cells (8).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid content was gravimetrically determined after extraction in organic solvant as previously reported (16) Lipolytic activity of isolated adipocytes and glucose uptake into fat tissue pieces.-Freshly isolated white adipocytes were used for the determination of lipolytic activity, by assessing the glycerol release in incubation medium containing 3.5 % bovine albumin, as previously described (4). The results were expressed as percentage of responses to 10 nM isoprenaline, which is independent of fat cell size and basal triglyceride breakdown (9). The previously described technique used for the determination of 2-deoxyglucose uptake into adipocytes (8) was adapted to small pieces of adipose tissues, incubated without previous collagenase digestion, and separation between internalized hexose from extracellular was performed by successive washings as for muscle (19) instead of the centrifugation through dynonylphtalate layer used for buoyant fat cells (8).…”
Section: Methodsmentioning
confidence: 99%
“…Animals and protocols.-Male Wistar rats or guinea pigs were housed and handled as already described (14). The oneweek continuous sc-administration of CL mg/kg body weight/day was performed with osmotic minipumps (Alzet 2001) implanted in the dorsal region.…”
Section: Methodsmentioning
confidence: 99%
“…This led us to quantify insulin responsiveness as increase over basal values of glucose metabolism. Lipogenesis.-Lipogenesis from [3-3 H]-glucose was determined by measuring the radioactivity incorporated into lipids after extraction in an organic phase, as previously described (14). Briefly, adipocytes were incubated 90 min in 400 μl KRBH containing 0.5 mM labeled glucose (0.15 μCi).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that long--term administration of CL 316,243 (CL), a highly selective b 3 -adrenoceptor agonist, largely reduced fat stores and retarded the development of obesity in young rats fed a high-fat diet [18], as well as reversed established diet-induced obesity in older animals [19][20][21]. Similar fat-reducing effect of CL was also described in adult non-obese rats [22,23].…”
Section: Introductionmentioning
confidence: 81%